The Impact of the PENA Program on the Digitalization of Women-Led MSMEs in Semarang - AMALIA, VIA (Journal of Technology Management and Technopreneurship (JTMT), 2025)
This study explores the impact of the PENA Program on the digitalization of women-led MSMEs in Semarang and its implications for empowerment and business sustainability. Using a qualitative approach, in-depth interviews were conducted with eleven female micro-entrepreneurs who are program beneficiaries. Thematic analysis was used to examine shifts in business practices, digital adaptation strategies, and how digital tools support women’s empowerment. The results show that the PENA Program has facilitated digital access through financial literacy training and mentorship. Digitalization has improved marketing, operational efficiency, and self-confidence among participants, contributing to greater empowerment and sustainable economic inclusion. However, challenges remain, including limited time, dual domestic and business roles, and inadequate infrastructure. Digital adaptation varied across participants depending on digital literacy and social support levels. The study concludes that enhancing digital literacy and adaptive mentoring is key to accelerating digital transformation among women entrepreneurs. This research highlights the critical role of integrated support programs in promoting inclusive, gender-responsive digitalization at the micro-enterprise level. It offers valuable insights for policymakers and practitioners aiming to strengthen women’s economic participation in the digital economy.